Analysis of Project Assignments on Cultural Arts Learning on Student Learning Independence - Mahfud Pageno; Nurul Aswar; Baderiah Baderiah (State Islamic Institute of Palopo, 2023)
This study aims to (1) determine the implementation of project assignments in cultural arts learning, and (2) determine the response of student learning independence in grade V elementary school project assignments. This research is designed in the form of qualitative descriptive research. The subjects in this study were class V teachers, and grade V students at SDN 60 Salubattang. Data were collected using observation, interview, and documentation study methods. Data is analyzed through four stages data collection, data reduction, data presentation, and verification. The results of this study show that (1) the implementation of project assignments given by teachers to students is collage artwork, whereas, in the implementation process, it is carried out with two meetings. Determine teacher grades using assessment guidelines based on observations during the process of creating a collage project assignment. (2) The response of students to the tasks given in the form of collages is very positive and enthusiastic, students are also willing to prepare tools and materials that will be used in the process of making collage fine artworks.